2020
DOI: 10.1111/bor.12435
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary glacier and sea‐ice history of northern Wijdefjorden, Svalbard

Abstract: The deglaciation history and Holocene environmental evolution of northern Wijdefjorden, Svalbard, are reconstructed using sediment cores and acoustic data (multibeam swath bathymetry and sub‐bottom profiler data). Results reveal that the fjord mouth was deglaciated prior to 14.5±0.3 cal. ka BP and deglaciation occurred stepwise. Biomarker analyses show rapid variations in water temperature and sea ice cover during the deglaciation, and cold conditions during the Younger Dryas, followed by minimum sea ice cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 122 publications
4
19
0
Order By: Relevance
“…(2015) found the smallest RI‐OH′ and largest RI‐OH residuals at the lowest SSTs and recommended to use RI‐OH′ rather than RI‐OH for polar oceans. Consequently, all subsequent validations of the RI‐OH′ paleothermometer focused on polar oceans (Allaart et al., 2020; Kremer et al., 2018; Liu et al., 2020; Park et al., 2019; Vorrath et al., 2020; J. Wu et al., 2020; see also Fietz et al., 2020 for a review). While the Iberian Margin is not presently under the influence of (sub)polar waters, it was during Heinrich events when the Polar Front reached this margin (Bard, Arnold, Maurice, et al., 1987; Eynaud et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2015) found the smallest RI‐OH′ and largest RI‐OH residuals at the lowest SSTs and recommended to use RI‐OH′ rather than RI‐OH for polar oceans. Consequently, all subsequent validations of the RI‐OH′ paleothermometer focused on polar oceans (Allaart et al., 2020; Kremer et al., 2018; Liu et al., 2020; Park et al., 2019; Vorrath et al., 2020; J. Wu et al., 2020; see also Fietz et al., 2020 for a review). While the Iberian Margin is not presently under the influence of (sub)polar waters, it was during Heinrich events when the Polar Front reached this margin (Bard, Arnold, Maurice, et al., 1987; Eynaud et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In temperate and polar oceans, the only two global core top studies to date have shown that RI‐OH and RI‐OH′ increase with increasing SST (Fietz et al., 2020; Lü et al., 2015). Only a few recent studies have used RI‐OH (Davtian et al., 2019; de Bar et al., 2019) and RI‐OH′ (Allaart et al., 2020; Fietz et al., 2020; Kremer et al., 2018; Vorrath et al., 2020; J. Wu et al., 2020) as SST proxies in sedimentary archives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore a direct comparison is not applicable to our spatiotemporal record, which targets naturally felled wood only. Other proxy‐based reconstructions of sea ice, such as those derived from the IP 25 biomarker, also suggest variability in sea ice cover during the Late Holocene associated with intermittent warm sea surface temperatures (Allaart et al., 2020; Jernas et al., 2013; Müller et al., 2012; Pawłowska et al., 2020; Sarnthein et al., 2003). Records of brine formation can be interpreted as a proxy for sea ice cover above basins, with a varied Late Holocene record from Storfjorden (Figure 1) suggesting episodic fluctuations between intense and reduced brine formation and concurrent sea ice cover variability (Rasmussen & Thomsen, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…2). Allaart et al (2020) reported north-south-trending ridges on bathymetric data in northern Wijdefjorden, but these consist either of recent glacial deposits following the trend of the fjord and are associated with a flat-lying top-basement reflection (Allaart et al 2020, figure 5) or of tightly folded, subvertical basement units of the Atomfjella Antiform (Manby 1990;Witt-Nilsson et al 1998). Based on these observations, we discuss three possible scenarios for the Billefjorden Fault Zone north of Wijdefjorden.…”
Section: Discussionmentioning
confidence: 99%